Diagnosis and Treatment in a Tertiary Hospital of a Series of Complex Genital Malformations Corresponding to Double Uterus with Obstructed Hemivagina and Ipsilateral Renal Agenesis - Troncon, Júlia Kefalás; Rosa-e-Silva, Júlio César; Miranda, Rayssa; Candido-dos-Reis, Francisco José; Poli-Neto, Omero Benedicto; Nogueira, Antônio Alberto (International Journal of Reproductive Medicine, 2018)
Aim. To evaluate the clinical features, diagnostic routine, treatment, and prognosis of patients with double uterus with obstructed hemivagina and ipsilateral renal agenesis at a University Hospital. Methods. A retrospective study analyzing the medical charts of outpatients with similar complex genital malformations seen at the University Hospital of the Ribeirão Preto Medical School from 1994 to 2015. Results. Fourteen patients were included in this retrospective study, all presenting with double uterus with obstructed hemivagina and ipsilateral renal agenesis. The main symptom was dysmenorrhea occurring shortly after menarche, and pelvic ultrasound was the examination of choice. The treatment consisted of resection of the vaginal septum, complemented by an abdominal approach in 5 cases. Complications of the syndrome observed in this case series included severe endometriosis, pelvic abscess, need for hysterectomy, and salpingectomy. Conclusions. Severe dysmenorrhea shortly after menarche is a typical symptom of this kind of malformation, even though the diagnosis of patients who present with fistulization of the vaginal septum can be delayed due to milder clinical features. Pelvic ultrasound can be considered the first-choice examination in diagnostic routine. Relief of pain and prevention of complications can be achieved successfully in most cases by resection of the vaginal septum.